Implementation of Digital Parenting on Early Childhood Gadget Addiction: A Scoping Review - Muspratiwi, Dea; Suryani, Suryani; Hidayati, Nur Oktavia (Poltekkes Kemenkes Palu, 2024)
The case of gadget addiction among children is quite alarming. Survey results from the Indonesian Child Protection Commission (KPAI) state that as many as 79% of children are allowed to use gadgets. In this case, the role of parents is very important in supervising children when using gadgets. Supervision in this case is by the digital parenting method used by parents in an effort to limit the use of gadgets in early childhood. This study aims to discuss some appropriate implementations in the application of digital parenting applied by parents to children's behavior in using gadgets. The method used in this research is a scoping review using two databases namely PubMed and Science Direct with Indonesian language articles, published from 2018-2022. The results obtained from 5 articles show that parents' experiences related to the implementation of digital parenting that can be used as an effort to prevent gadget addiction are the role of parents in mentoring and time management in the use of gadgets in early childhood. The conclusion of this study is that the implementation of digital parenting through the role of parents in mentoring and implementing time management can be applied in preventing gadget addiction in early childhood.